Successful Ablation of Cavotricuspid Isthmus-dependent Atrial Flutter Guided by Contact Force Vector in a Patient After a Tricuspid Valve Replacement - Goto, Eri (Indian Pacing Electrophysiol J, 2014)
A 46-year-old man after a tricuspid valve replacement due to traumatic severe tricuspid regurgitation developed cavotricuspid isthmus-dependent counterclockwise atrial flutter. During a linear ablation using a contact force-sensing irrigated ablation catheter, the flutter could be terminated by a radiofrequency application within a deep pouch just below the bioprosthetic tricuspid valve.